IDEOLOGI RANA YADNYA DALAM KIDUNG RASANG PELOG KAJIAN SEMIOTIKA - Santika, I Made; Suryati, Ni Made; Putra, Ida Bagus Rai (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Kidung Rangsang Pelog (KRP) is a literary work in the form of a kidung containing the ideology of rana yadnya. KRP was written by Ida Padanda Made Sidemen, a great Balinese author of the 20th century. This literary work was born at the request of Ida Cokorda Puri Satria Denpasar (Puri Agung Denpasar). KRP as a whole contains the events of Puputan Badung and leadership teachings. This study aims to reveal the ideology of rana yadnya in the KRP text using Michael Riffaterre's semiotic theory. The method used in this study is a qualitative method. The data collection stage was carried out using the listening method with the basic technique of free involvement. The method and technique of data analysis used is the descriptive analytical method. The method and technique of presenting the results of the data analysis used is the informal deductive-inductive method. The results of the data analysis show that through heuristic and hermeneutic reading of the KRP text, several topics were found related to the ideology of rana yadnya 'war as a sincere sacrifice', namely, a knight who masters the science of bravery against the enemy, the nature of being born as a knight, the struggle of the Badung army against the Dutch, the obligation to fight for a knight. The ideology of rana yadnya 'war as a sincere sacrifice' was inserted by the text producer through the description of the Puputan Badung story and leadership teachings in the KRP text. The ideology of rana yadnya in the KRP text is intended as a reminder of the nature of being a knight and a record of the struggle of ancestors so that a knight does not hesitate to fight to defend the honor and sovereignty of the nation.